Effect of early intervention on functional outcome at school age: Follow-up and process evaluation of a randomised controlled trial in infants at risk. (March 2017) - Hamer, Elisa G.; Hielkema, Tjitske; Bos, Arend F.; Dirks, Tineke; Hooijsma, Siebrigje J.; Reinders-Messelink, Heleen A.; Toonen, Rivka F.; Hadders-Algra, Mijna
Abstract: Background: The long-term effect of early intervention in infants at risk for developmental disorders is unclear. The VIP project ( n = 46, originally) evaluated by means of a randomised controlled trial the effect of the family centred early intervention programme COPCA (Coping with and Caring for infants with special needs) in comparison to that of traditional infant physiotherapy (TIP). Aims: To evaluate the effect of early intervention on functional outcome at school age. Methods and procedures: Parents of 40 children (median age 8.3 years) participated in this follow-up study. Outcome was assessed with a standardised parental interview (Vineland Adaptive Behaviour Scale) and questionnaires (Developmental Coordination Disorder Questionnaire, Child Behaviour Checklist, Utrechtse Coping List, and questions on educational approach). Quantified video information on physiotherapeutic actions during infancy was available. Outcomes and results: Child functional outcome in the two randomised groups was similar. Process evaluation revealed that some physiotherapeutic actions were associated with child mobility and parental educational approach at follow-up: e.g., training and instructing were associated with worse mobility. Conclusions and implications: Functional outcome at school age after early intervention with COPCA is similar to that after TIP. However, some specific physiotherapeutic actions, in particular the physiotherapist's approach, are associated with outcome. What this paper adds: Early intervention is generally applied in infants at risk for developing disorders, with the aim of improving overall functional outcome. However, little is known on the long-term effect. The VIP project evaluated by means of a randomised controlled trial the effect of the family centred early intervention programme COPCA (Coping with and Caring for infants with special needs) in comparison to that of traditional infant physical therapy (TIP). Outcome at 18 months corrected age was virtually similar. Process evaluation of the physiotherapy actions revealed that some characteristics of COPCA were associated with improved developmental outcome at 18 months. This paper presents data on functional outcome at school age (median 8.3 years) in 87% of the original participants. Outcome of infants who received three months of COPCA and that of infants who received three months of TIP was similar. Yet, parents of families who had received the COPCA intervention still more often used a trial and error approach when the child learned a new skill than parents of children who had received TIP. Process evaluation showed that more time spent on caregiver training and strict instructions during early intervention was associated with worse mobility. Four other physiotherapeutic actions were associated with parental educational approach. None of the neuromotor actions were associated with child outcome at school age. We conclude that long-term outcome after three months of COPCA or TIP is similar. However, our study does suggest that the professional approach of the physiotherapist can make a difference. Highlights: On RCT-level, functional outcome at school age after early intervention with COPCA was similar to that after TIP Process evaluation revealed that more time spent on caregiver training and instructions was associated with worse later mobility The physiotherapist's approach (including coaching and feedback) was associated with later parental educational approach